Fistula Formation 6 Years after Removal of Infected Pacemaker Leads - Schroeter, Thomas; Kiefer, Philipp; Sauer, Matthias; Mohr, Friedrich Wilhelm (The Thoracic and Cardiovascular Surgeon Reports, 2015)
We describe a case of a male patient who presented with a chronic ulcer below the left clavicle. Six years before the present admission a permanent pacemaker, including leads, was explanted related to endocarditis. The initial working hypothesis suspected an infected sebaceous gland as the cause of ulceration. After two periods of unsuccessful surgical treatment of the gland, further examination identified a small pacemaker lead fragment underneath the articulation between sternum and clavicle as a possible reason.
Keywords: endocarditis; pacemaker; fistula; infection